Eigenvalues of Geometric Operators Under the List’s Flow - Ma, Bingqing (Communications in Mathematics and Applications, 2013)
We consider the evolution equation of eigenvalues of the operator -Δ+cS under the (normalized) List’s flow. As an application, we derive monotonicity formulas for eigenvalues of -Δ+12S.